Marriage of first cousin and nullity of marriage: Canon 1091 - Waters, Ian (CLSA advisory opinions, 2001-2005, 2001)
The first cousins, both baptized non-Catholics, married in 1970. Cound a case for nullity of marriage be considered on the basis that the canons on consanguinity were not explicitly listed as exclusions for non-Catholica in the 1917 code?